A identidade judaico brasileira, a partir de Porto Alegre, na iminência da fundação de Israel (1945-1950) - Rotta, Helen Rocha (2018)
The presence and formation of Jewish identity in Brazil is usually discussed under the point of view of some great basic landmarks about the group, such as anti-semitism and its development in Americas. However, there are other perspectives about specific and daily elements, which are mainly related to the dynamics of community life of the Jews and Jewish, and how they were on Brazilian land. This research aimed to analyze these other possibilities in order to understand the formation of Jewish identity in Brazil during the period from 1945 to 1950. Furthermore, it took into account the importance of this period due to the end of authoritarian regimes, both in Brazil and Europe, the revealed traumas of the Shoah and the creation of Israel State as a Jewish place. From Porto Alegre city – third largest capital in Jewish presence in Brazil – it is possible to note that the face with so many changes that focus directly on Judaism, the Jewish identity in the diaspora brazilian appears to have faced long debates and internal disputes, seeking a reflection about their individual values and its consequences in the common group. These elements can be especially inferred from internal circulation journals in the Jewish community in Porto Alegre, and in the Hatikva, DROR-Zionist Socialist Youth Organization, Hamagbit and Kol Israel Almanac-Group Betar.